Making Sense of History - Şen, Gül, author.
1 online resource
Keywords: In Making Sense of History: Narrativity and Literariness in the Ottoman Chronicle of Naʿīmā, Gül Şen offers the first comprehensive analysis of narrativity in the most prominent official Ottoman court chronicle. Using an interdisciplinary approach that combines methods from history and literary studies, Şen focuses on the purpose and function of the chronicle—not just what the text says but why Naʿīmā wrote it and how he shaped the narrated reality on the textual level. As a case study on the literalization of historical material, Making Sense of History provides insights into the historiographical and literary conventions underpinning Naʿīmā’s chronicle and contributes to our understanding of elite mentalities in the early modern Ottoman world by highlighting the author’s use of key concepts such as history and time.